(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article examines translation studies as a separate scientific discipline. It looks at the fundamental ideas and techniques that distinguish translation as a study and an art. The study emphasizes how crucial it is for tranlators to comprehend contextual, linguistic, and cultural aspects. Through an examination of diverse theories and methodologies, the article hopes to clarify the ways in which translation studies advance our comprehension of language and communication. The importance of translation in promoting cross-cultural understanding and international ties is ultimately highlighted by this investigation.